2015
DOI: 10.1145/2816795.2818086
|View full text |Cite
|
Sign up to set email alerts
|

A model of local adaptation

Abstract: Figure 1: Processing steps of our spatial adaptation model. First, optical glare is simulated to produce a retinal image. Then, the local luminance adaptation map is computed using our novel adaptation model. The plots below show the luminance profile for the pixels marked with the dashed-orange line. Note that the eye cannot adapt to small highlights as shown by the flattened blue curve in the "adaptation luminance" plot. As one of the applications, the adaptation map can be used to estimate the smallest visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…In order to develop a generic model that can truthfully predict PDR, sensory and cognitive processes involved in extraction of this attribute from complex stimuli need to be taken into account. Previous research has shown that the area of the brightest patches and the image topology affect the perception of lightness and contrast [17,19,26], and therefore should be considered in constructing such a PDR model. Furthermore, image contrast and colorfulness are important factors in visual perception and, based on previous findings [8,11,24,25], could be involved in the process related to the extraction of observed image attributes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop a generic model that can truthfully predict PDR, sensory and cognitive processes involved in extraction of this attribute from complex stimuli need to be taken into account. Previous research has shown that the area of the brightest patches and the image topology affect the perception of lightness and contrast [17,19,26], and therefore should be considered in constructing such a PDR model. Furthermore, image contrast and colorfulness are important factors in visual perception and, based on previous findings [8,11,24,25], could be involved in the process related to the extraction of observed image attributes.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent work, Vangorp et al defined a model of local adaptation and use it to measure dynamic range as the ratio between the brightest and darkest image region in which people can still see some details [26]. The model predicts the maximum visible dynamic range for any given scene, based on both glare and local adaptation.…”
Section: Image Contrastmentioning
confidence: 99%
“…While the individual neural units of the HVS are limited to respond in a range of about 1.5 log units [SW12], this capacity is achieved through the utilization of local adaptation mechanisms, such as spatially varying neural gain controls. The local processing makes it possible to restrict adaptation to an area of less than 0.5 visual degrees [VMGM15]. Furthermore, by adapting over time using e.g.…”
Section: Perceptual Motivation Of Tone-mappingmentioning
confidence: 99%
“…The response range of the individual neural units is limited to around 1.5 log 10 units [232]. However, adaptation can be restricted to an area of less than 0.5 visual degrees [251], so that the effective dynamic range over the observed scene is larger, around 3.7 log 10 units [141,207]. Moreover, we constantly use saccadic eye movements, and adapt to the lighting close to the focal point both in focus and exposure.…”
Section: The Dynamic Range Of the Hvsmentioning
confidence: 99%